Unveiling Wunderlich syndrome: Diagnosis and management of a rare spontaneous renal hematoma - Rebecca Merrill; Pete Jordanides; Jessica Krizo; Erin L. Simon (JEM Reports)
Background: Wunderlich syndrome (WS) is a rare condition that is described as an atraumatic, spontaneous renal hemorrhage in the perirenal space. Symptoms typically present as nondescript flank pain, but a flank mass and hypovolemic shock are also possible. Computed tomography (CT) imaging with intravenous contrast should be the modality of choice to diagnose WS, with recent studies highlighting the efficacy of transcatheter arterial embolization (TAE) as the preferred treatment over surgery. WS is often secondary to conditions such as renal neoplasms, vascular diseases, and infections, necessitating adequate follow up to determine the etiology. Case report: We present the case of a 79-year-old woman presenting to the emergency department (ED) with left flank pain. Computed tomography with angiography revealed a large left renal subcapsular hematoma with perinephric and retroperitoneal extension with active extravasation, characteristic of Wunderlich syndrome. The patient was treated emergently with transcatheter arterial embolization of the lower polar branch of her left renal artery. In the ED, WS can present with a variety of non-specific symptoms, making the diagnosis challenging for emergency physicians. Why should an emergency physician be aware of this?: Wunderlich syndrome is a rare, sudden, and life-threatening emergency that requires prompt diagnosis, as the hematoma can spread to the perinephric space leading to massive internal hemorrhage. Causes and presenting symptoms are variable, with flank pain being a common symptom. CT or MRI imaging is necessary for diagnosis, and embolization is often the treatment of choice to avoid further complications.